PENGARUH BUTGERTARY GOAL CHARACTERISTICS, STRUKTUR DESENTRALISASI TERHADAP KINERJA APARAT PEMDA DENGAN BUDAYA PATAERNALISTIK SEBAGAI VARIABEL MODERATING (Studi Kasus Pada Dinas-Dinas Kota Dumai) - Pratidina, Dwinta; Nur Dp, Emrinaldi; ', Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Some previous studies conducted on the budgetary goal characteristics both on the private as well as on public sectors on the local government officials indicated inconsistent results. This study aimed at re-examining the effect of budgetary goal characteristics on the local government officialsand also to examine whether paternalistic culture could act as moderating variables in the public sector organizations.The object of local government officials on 14 different institutional agencies in the local government in Dumaicity consisting of the top manager, middle manager, as well section head office and all of which role in budgeting. The samples were determined based on stratified random sampling. The data were collected by using survey questionaire. The hypothesis was tested by using multiple regression analysis and moderated regression analysis.The results indicated that (budgeting participation, budget goal clarity, budgetary evaluation, and budget goal difficulty) had a positive and significant effect on the local government officials performance. Budgetary feedback and decentralized Structurehad no effect on the local government officials performance. The study also resulted that budget goal difficulty and decentralized structure had significant effect on the the local government officials performances with paternalistic culture acted as moderating variables.Keywords: Budgetary, Decentralized, government and Paternalistic